Relationships between thinking skills and left, right and whole brain learning styles - Chua, Y.P. (Common Ground Publishing, 2003)
The purpose of the present study were to explore whether: 1) the right brain learning style is related to creative thinking and 2) the left brain learning style is related to critical thinking. In this study, brain learning style was measured by the Yanpiaw 'Brain Style' test (YBRAINS) and the Styles of Learning and Thinking test (SOLAT), while creative thinking and critical thinking were measured by three thinking skills instruments, the Torrance Test of Creative Thinking (TTCT), the Watson-Glaser Critical Thinking Appraisal (WGCTA) and the Yanpiaw 'Creative-Critical Styles' test (YCREATIVE-CRITICALS). As the second purpose, this study permitted analyses of the relationships between 1) the two types of brain learning style tests and 2) the three types of thinking skills tests. The five instruments were administered to 102 undergraduates. Results indicated that TTCT scores were positively correlated with right brain style scores of the YBRAINS and SOLAT, while the WGCTA scores were positively correlated with left brain style scores of the YBRAINS and SOLAT. Results also indicated positive relationships between the two brain styles tests on both left and right brain scores. The results demonstrated that the left brain learning style is related to critical thinking, while the right brain learning style is related to creative thinking. The present data are consistent with the notions that people who learn and think with right brain are creative. Since competence in creative thinking and critical thinking skills are essential to nearly every aspect of learning in every society, educators should implement whole brain learning strategies, instead of encourage merely the left, or the right brain learning strategies.